2013
DOI: 10.1139/er-2013-0040
|View full text |Cite
|
Sign up to set email alerts
|

An introduction to Canada’s boreal zone: ecosystem processes, health, sustainability, and environmental issues

Abstract: The boreal zone and its ecosystems provide numerous provisioning, regulating, cultural, and supporting services. Because of its resources and its hydroelectric potential, Canada's boreal zone is important to the country's resource-based economy. The region presently occupied by Canada's boreal zone has experienced dramatic changes during the past 3 million years as the climate cooled and repeated glaciations affected both the biota and the landscape. For about the past 7000 years, climate, fire, insects, disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
224
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 293 publications
(248 citation statements)
references
References 130 publications
(128 reference statements)
1
224
0
Order By: Relevance
“…As of 2011, there were 17 active and 7 closed or decommissioned pulp and paper mills in the boreal portion of the commercial forest ( fig. 3 in Brandt et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…As of 2011, there were 17 active and 7 closed or decommissioned pulp and paper mills in the boreal portion of the commercial forest ( fig. 3 in Brandt et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Knowledge on the extent, condition, and management of forest resources is critical to meet both national [3,4] and international [5] expectations of sustainable forest management and to support reporting requirements. In addition, the magnitude of harvest events, and the type of harvest (clearcut or selective cut), has implications to carbon budget modeling.…”
Section: Introductionmentioning
confidence: 99%
“…The boreal forest is a critical habitat for North American wildlife (Blancher 2003, Blancher and Wells 2005, Brandt et al 2013, and population declines in many bird species have been partially attributed to harvest management (e.g., Schmiegelow and Monkkonen 2002). We found that more than half of the boreal landbird species responded similarly to disturbances by fire and harvest, perhaps attesting to both the success of management efforts to emulate natural disturbances, as well as the resilience of many boreal birds (e.g., Schmiegelow et al 1997, Lemelin et al 2007.…”
Section: Resultsmentioning
confidence: 99%